NEW ANTITRYPANOSOMAL TETRANOTRITERPENOIDS FROM AZADIRACHTA INDICA - Githua, Mercy; Hassanali, Ahmed; Keriko, Joseph; Ndungu, Mary; Murilla, Grace; Nyagah, Gathu (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Organic extracts of the leaves of Azadirachta indica A. Juss. yielded ten antitrypanosomal terpenoids. Three of these (1 – 3), are novel and are derivatives of nimbolide and nimbin. They were extracted from chloroform fraction of methanol extract. These compounds were found to exhibit strong antitrypanosomal activities against Trypanosoma brucei rhodesiense with MIC values ranging of 6.9, 15.6 and 7.8 Âµg/ml respectively and were more active than Cymerlarsan ( a standard drug), which had an MIC value of 187.5 Âµg/ml when tested against T. b. rhodesiense The structures were elucidated by spectroscopic methods including; NMR, MS, UV and IR.